Study on the Level of Glucose, Hb1ac, Urea, Creatinine, and Complications in Patients with Type 2 Diabetes during Several Periods during the Disease - AlFatlawi, Mustafa Hamza; Alquraishi, Mohammed K. S.; Hammood, Samah Amer (Medical Science Journal for Advance Research, 2026)
Background & objective: Diabetes mellitus (DM) is a growing epidemic with global proportions. It is estimated that in 2019, 463 million adults aged 20-79 years were living with DM. The latest evidence shows that DM continues to be a significant global health challenge and is likely to continue to grow substantially in the next decades, we attempted to shed light on the Compare between patients with diabetes mellitus type 2 in different period of the disease with respect to glucose level, HbA1c and complications correlated with diabetes mellitus and the treatment. Methodology: The study included collecting information on 80 samples from people with type 2 diabetes, which were divided into four groups, group _A: 20 samples from patients with diabetes whose duration of infection was less than 5 years, group _B: 20 samples from patients with diabetes who had the disease for less than 10 years and more than 5 years, group _C: 20 samples from patients with diabetes who had the disease for less than 15 years and more than 10 years, group _D: 20 samples from diabetic patients who had the disease for more than 15 years. Results: The study showed for them in terms of the level of glucose, HbA1c, urea, and creatinine, as significant differences were found in the levels of these indicators as the duration of the infection increased. We also monitored the patients in terms of the type of treatment used during these periods and the diseases before and after diabetes. It was found that the longer the period of diabetes, the greater the risk of exposure to chronic diseases associated with diabetes. Conclusions: Through our study, it is clear that diabetes is a disease that develops in those infected with it, and this development of the disease leads to other complications that can affect the rest of the body’s organs, such as the eyes, heart, and kidneys.